COVID-19 Pandemic and Performance: Empirical study of Integrated Remote Site Management services in Dubai, United Arab Emirates - Avdic, Senaj; Elsaman, Hosam Azat; Gernal, Liza (JPAIR Multidisciplinary Research, 2021)
Generally and in the UAE, businesses worldwide are particularly affected by the COVID-19 pandemic. The SME companies in Dubai UAE faced a very tough challenge to deal with the new circumstances of lockdown and curfews in running the international business. The purpose of the current study was to analyze the effect of the COVID-19 pandemic on Business Performance. The theoretical frameworks for this study are Process Theory of Internationalization (PTI), Uppsala-model (the U-model), and internalization theories and the link with IB theories applications nowadays. The quantitative study applied a nonexperimental, deductive approach and explanatory correlation design, and Snowball sampling was used to select stakeholders of integrated remote site management (IRSM) services in Dubai, UAE. Data was collected at a single phase using a cross-sectional survey instrument and analyzed using inferential statistics with the aid of SPSS. The survey results revealed that the COVID-19 pandemic did not significantly change the efficiency performance of the IRSM stakeholders. Stakeholders’ confidence in their strategic leaders did not decrease while working under the constraints of the COVID-19 pandemic. The study did not account for any changes in employee or leaders’ behavior over time. This Empirical study findings add value to the limited literature on the correlation between the COVID-19 pandemic and the strategic leadership of international businesses. The paper’s practical implications would be further study on strategic leadership in IB and efficiency performances during global pandemics.